Sikap Belajar Mahasiswa Ditinjau Dari Keaktifan Berorganisasi Dan Kemandirian Belajar Mahasiswa Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2013/2014 - Rusydina Arsyadi, Harini, Drs. Muhammad Yahya, M.Si (2016)
The purpose of this study to determine: 1 ) Effects of liveliness organize of student learning attitude in accounting student in generation 2013/2014, 2 ) The effect of student learning independence of student learning attitude in accounting student in generation 2013/2014, and 3 ) The liveliness organize and student learning independence student learning attitude in accounting student in generation 2013/2014. This research included quantitative descriptive research type with the withdrawal of the conclusion through statistical methods. The population in this study were students association of accounting student of muhammadiyah university of surakarta in generation 2013/2014 as many as 77 students. The sampling technique using Sampling kuota as many as 62 students. The necessary data and documentation obtained through a questionnaire that has previously been tested by validity and reliability testing. Data analysis technique used is multiple linear regression, t-test, F test, R2, and the relative contribution and effective. The results of the regression analysis regression line equation is obtained; Y = 13.350 + 0. 226 X1 + 0.420 X2. The equation shows that the decision of the student learning attitude are affected by liveliness organize and student learning independence. The conclusions drawn are: 1) The liveliness organize of student learning attitude of study acceptable. It is based on the test of hypothesis t-test Note that t hitung > t tabel, 2.682 > 2.001 and value signnifikasi < 0.05, of 0.009, i.e. the relative contributions 37% and the effective contribution of 16.13% ; 2) student learning independence of student learning attitude of study acceptable. This is based on the testnof hypothesis t-test note that t count > t table, namely 3.992 > 2.001 value and significance of < 0.05 of 0.000, i.e. the relative contribution 63 % and the effective contribution of 27.34 %. 3) liveliness organize and student learning independence of student learning attitude of study acceptable. This is based on F test note that Fcount > Ftable, namely 22.723 > 3,153 significance and value, i.e. 0.05 < 0.000. 4) The coefficient of determination (R2) of 0.435 showed that the magnitude of the liveliness organize and student learning independence against the student learning attitude is of 43.5%, while the rest in influence other variables.